2015
DOI: 10.1111/ter.12152
|View full text |Cite
|
Sign up to set email alerts
|

Critical taper behaviour and out‐of‐sequence thrusting on orogenic wedges – an example of the Eastern Alpine Molasse Basin

Abstract: We demonstrate that increasing erosion during the kinematic evolution of a thrust wedge will lead to out-of-sequence thrusting as a result of backwards critical taper movement. In-sequence Accepted ArticleThis article is protected by copyright. All rights reserved. thrusting in the Subalpine German Molasse Basin built a critical-tapered foreland Coulomb thrust wedge. Later out-of-sequence thrusts dissected all but the frontal duplex stacks. The footwall/hangingwall relation visible on seismic data proves the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
(32 reference statements)
1
16
0
Order By: Relevance
“…Since the youngest AHe ages are associated with internal tectonic slices of the Subalpine Molasse (Figs. 2, 3, and 4), we can infer the occurrence of break-back thrusting, a characteristic feature, which has been confirmed along the entire Subalpine Molasse of the Central Alps based on thermochronological data and cross section restoration (von Hagke et al, 2012(von Hagke et al, , 2014Ortner et al, 2015;Schuller et al, 2015), but has been argued for as early as the 1930s (Haus, 1935(Haus, , 1937. The break-back thrusts are supposedly younger than the development of the frontal triangle zone, which formed the active northern deformation front from ca.…”
Section: Upscaling: Implications For Late Orogenic Processes At the Smentioning
confidence: 61%
See 3 more Smart Citations
“…Since the youngest AHe ages are associated with internal tectonic slices of the Subalpine Molasse (Figs. 2, 3, and 4), we can infer the occurrence of break-back thrusting, a characteristic feature, which has been confirmed along the entire Subalpine Molasse of the Central Alps based on thermochronological data and cross section restoration (von Hagke et al, 2012(von Hagke et al, , 2014Ortner et al, 2015;Schuller et al, 2015), but has been argued for as early as the 1930s (Haus, 1935(Haus, , 1937. The break-back thrusts are supposedly younger than the development of the frontal triangle zone, which formed the active northern deformation front from ca.…”
Section: Upscaling: Implications For Late Orogenic Processes At the Smentioning
confidence: 61%
“…The latter consists of south-dipping imbricated thrust sheets and in large parts north-dipping backthrusts forming a triangle zone at the transition to the Plateau Molasse ( Fig. 1b; Berge and Veal, 2005;Fuchs, 1976;Müller et al, 1988;Ortner et al, 2015;Schuller et al, 2015;Sommaruga et al, 2012). The Subalpine Molasse started to become incorporated into the orogenic wedge shortly after deposition in Oligocene times (Hinsch, 2013;Kempf et al, 1999;Pfiffner, 1986).…”
Section: Evolution Of the Central Alps And Their Forelandmentioning
confidence: 99%
See 2 more Smart Citations
“…They deciphered a significantly high c. 12 mm a 21 slip rate and a c. 7 mm a 21 rate of shortening in the horizontal direction from this out-of-sequence thrust during the Holocene. De Sarkar et al (2014) concluded that profound erosion and a critical taper condition produced this out-of-sequence thrust (see also Schuller et al 2015). However, debate has not resolved about how far erosion can control the (Himalayan) tectonics (see brief review in Whipple 2014).…”
Section: Uttarakhand Garhwal and Kumaun (India)mentioning
confidence: 99%